2018
DOI: 10.21307/jofnem-2018-031
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Molecular Characterization of Labrys filiformis n. sp. (Rhabditida: Tylenchidae) from Iran

Abstract: Labrys filiformis n. sp., the second species of the rare genus Labrys, was recovered from natural forests of Gilan province and is described based upon morphological and molecular characters. The new species is characterized by its smooth cuticle under light microscopy, lateral field with two incisures forming a single plain band, lip region continuous with body contour, dorso-ventrally flattened and forming four poorly prominent lobes, having a dorso-ventrally narrower protuberant labial plate laterally exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…Troccoli and Geraert (1995) reported a population of S. indica from Papua province of Indonesia which has a median bulb with a developed valve, elongate cylindrical pharyngeal bulb and a filiform tail, which is narrower at the distal end. It seems that the Papuan population has remarkable differences compared with the type population of S. indica , specifically the Papuan population has a distinct Labrys ‐type cephalic region and the labial disk (Konani, Panahandeh, Pourjam, Álvarez‐Ortega, & Pedram, 2018; Panahandeh, Abolafia, et al, 2018b; Qing & Bert, 2018) (see Figure a in Troccoli & Geraert, 1995). Therefore, only the original data of S. indica were used in our morphological comparisons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Troccoli and Geraert (1995) reported a population of S. indica from Papua province of Indonesia which has a median bulb with a developed valve, elongate cylindrical pharyngeal bulb and a filiform tail, which is narrower at the distal end. It seems that the Papuan population has remarkable differences compared with the type population of S. indica , specifically the Papuan population has a distinct Labrys ‐type cephalic region and the labial disk (Konani, Panahandeh, Pourjam, Álvarez‐Ortega, & Pedram, 2018; Panahandeh, Abolafia, et al, 2018b; Qing & Bert, 2018) (see Figure a in Troccoli & Geraert, 1995). Therefore, only the original data of S. indica were used in our morphological comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Following our continuing study of tylenchid nematodes in cultivated and natural habitats of northern Iran (the history in Panahandeh, Pourjam, et al, 2018a; Panahandeh, Abolafia, et al, 2018b), one population of the genus Sakia was recovered from decaying bark and wood samples from undisturbed Sisangan forest in northern Iran. The species is herein described as S. sisanganensis n. sp.…”
Section: Introductionmentioning
confidence: 99%
“…The taxonomic studies on the members of the family Tylenchidae reported from Iran are well documented and discussed in Karegar (2018). Some other species of the genera Miculenchus Andrássy, 1959 (Panahandeh et al ., 2019a), Coslenchus Siddiqi, 1978 (Hosseinvand et al, 2019), Labrys Qing & Bert, 2018 (Panahandeh et al ., 2018, 2019b), Sakia Khan, 1964b (Panahandeh et al ., 2019c), Basiria Siddiqi, 1959 (Eisvand et al ., 2019) and Malenchus Andrássy, 1959 (Jalalinasab et al ., 2019) have since been reported or described from Iran through morphological and molecular studies. The present study aims to describe the newly recovered species, named Thada populus n.…”
Section: Introductionmentioning
confidence: 99%
“…Its members are commonly found in vast ecological niches viz . soil, algae, fungi, and plant material ( Panahandeh et al, 2018 ). Currently, approximately 44 genera and 412 species are known in this family ( Qing and Bert, 2019 ).…”
mentioning
confidence: 99%
“…Traditionally, most tylenchids were identified based solely on morphological characters ( Geraert, 2008 ), which led to taxonomic confusions within the family ( Qing and Bert, 2019 ). However, in recent years, DNA-based techniques have been extensively used for taxonomic studies of tylenchids ( Bert et al, 2010 ; Pereira and Baldwin, 2016 ; Pereira et al, 2017 ; Pedram et al, 2018 ; Panahandeh et al, 2018, 2019 ; Qing and Bert, 2019 ).…”
mentioning
confidence: 99%